2021
DOI: 10.1007/s10120-020-01150-9
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancy between endoscopic and pathological ulcerative findings in clinical intramucosal early gastric cancer

Abstract: Background Ulcerative finding (UL) is one of the factors that define the indication and curability of endoscopic resection (ER) in early gastric cancer (EGC). Discrepancies between endoscopic UL (cUL) and pathological UL (pUL) sometimes occur in clinical practice. The aim of this study was to investigate the discrepancy rate in UL diagnosis and the risk factors associated with such discrepancies. Methods Patients with clinical intramucosal (cT1a) EGC who underwent ER or surgery between September 2002 and Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…17,34,35 In agreement with reported data, our study demonstrated that the depressed pattern, nodular surface, surface redness, lesion size >2 cm, and location in the upper third of the stomach were risk factors in pathological upgrading. 23,36,37 EGCs located in the lower third of the stomach, especially in the antrum, might be detected easily, but for those in the upper third, detection may be difficult due to denser mucosal folds, thinner stomach, and limited endoscopic visual fields. 36 Ideally, one would incline to have a validated noninvasive biomarker to predict cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,34,35 In agreement with reported data, our study demonstrated that the depressed pattern, nodular surface, surface redness, lesion size >2 cm, and location in the upper third of the stomach were risk factors in pathological upgrading. 23,36,37 EGCs located in the lower third of the stomach, especially in the antrum, might be detected easily, but for those in the upper third, detection may be difficult due to denser mucosal folds, thinner stomach, and limited endoscopic visual fields. 36 Ideally, one would incline to have a validated noninvasive biomarker to predict cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…Ulceration or ulcer scar was considered positive after excluding those caused by the biopsy. 23 Remarkable redness was defined as discoloration on the mucosal surface of the lesion compared to the surrounding mucosa, and uneven surface was defined as the presence of irregularly raised or nodular mucosa. 24 , 25 Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Ultimately, however, it must be confirmed by pathological examination findings of the resected specimen. Endoscopic diagnosis is difficult in the absence of a mucosal break [ 53 ], and ulcer-negative endoscopy findings with ulcer-positive pathology findings were reported in 4.6%–5.5% of cases [ 54 , 55 ].…”
Section: Application Of Standard Pathology Reportmentioning
confidence: 99%